2019
DOI: 10.5539/gjhs.v11n12p55
|View full text |Cite
|
Sign up to set email alerts
|

Non-Governmental Organisations Personnel, Social Workers and Religious Leaders’ Perspectives on the Risk Factors of Alcohol Abuse Amongst the Youth: The Case of the Northern Region of the Republic of Namibia

Abstract: This qualitative study aimed to explore and describe the perceptions of Non-Governmental Organisations personnel, social workers and religious leaders on the risk factors of alcohol abuse amongst youth in the Northern region of the Republic of Namibia. In order to pursue this aim, a multiple case study design was used. Substance abuse is a predominant social and health problem which calls the attention of different partners from different disciplines across the globe to address it. Substance abuse, in particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Learners also consumed alcohol at parties, friend’s places, clubs and communities. These findings confirm ease of alcohol access by learners both around schools and in the communities, consistent with studies conducted in South Africa [ 21 , 24 , 31 ] and other countries [ 39 , 59 , 60 ]. Hasheena et al [ 28 ], reported that 62% of grade 8 learners, 81% of grade 10 learners and 92% of grade 12 learners reported that alcohol was easily accessible to them in Namibia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Learners also consumed alcohol at parties, friend’s places, clubs and communities. These findings confirm ease of alcohol access by learners both around schools and in the communities, consistent with studies conducted in South Africa [ 21 , 24 , 31 ] and other countries [ 39 , 59 , 60 ]. Hasheena et al [ 28 ], reported that 62% of grade 8 learners, 81% of grade 10 learners and 92% of grade 12 learners reported that alcohol was easily accessible to them in Namibia.…”
Section: Discussionsupporting
confidence: 91%
“…Hasheena et al [ 28 ], reported that 62% of grade 8 learners, 81% of grade 10 learners and 92% of grade 12 learners reported that alcohol was easily accessible to them in Namibia. Studies have reported that the more alcohol outlets within school vicinity and in the communities, the more likely youths will engage in drinking alcohol, and this has been reported in countries such as South Africa [ 21 , 24 , 31 ], Namibia [ 39 ], Brazil [ 59 ] and Canada [ 60 ]. Therefore, the wide availability of alcohol outlets around schools and the lack of regulating policies contribute to the normalisation of alcohol use [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, family has the role to mentor and teach young people to not engage in excessive drinking. However, in most rural areas, young people grow up in families that excessively abuse alcohol and youths see that as an acceptable behaviour (Rapholo et al 2019). According to Matlakala et al (2019b), youths lack role models and discipliners as they indulge in alcohol abuse with their parents.…”
Section: Learning From Parentsmentioning
confidence: 99%
“…This assumption is supported by Rapholo et al (2019) who averred that young people need to be vigilant when choosing friends.…”
Section: Peer Pressurementioning
confidence: 99%